A new model of trajectory in eddy current separation for recovering spent lithium iron phosphate batteries. (December 2019) - Bi, Haijun; Zhu, Huabing; Zu, Lei; Bai, Yuxuan; Gao, Song; Gao, Yong
Highlights: The force and kinematics models of different crushed product is established. An iterative method is used to improve the accuracy of the model. Displacement interval replaces disengagement angle as a separating index. Test results are consistent with simulation results. Abstract: Eddy current separation (ECS) is an environment-friendly technology for separating nonferrous metallic particles whose size was from 2 mm to 10 mm. No wastes are generated in ECS. ECS quality of nonferrous metals from solid wastes is rather low in the production practice of spent lithium iron phosphate (LFP) batteries recovering. Repeating separation even manual sorting is required in the production. The traditional method of falling point prediction based on eddy current mechanics uses equivalent acceleration to replace separation motion curves. These curves have low precision and are unsuitable for predicting the motion trajectory of small particle size of sorted materials. In this work, eddy current separation of positive and negative plates in a crushed product of spent lithium iron phosphate battery is used as an example to establish the force and kinematics models of different materials in the eddy current separation. An iterative method, rather than average speed method, is used to improve the accuracy of the model. Displacement interval replaces disengagement angle as a separating index to improve the model's intuitiveness and practical guidance. In the range of 2–20 mm, test results are consistent with simulation results. The copper and aluminium foils at a magnetic roller speed of 800r/min can be separated to a maximum particle size ratio of 1.72, and the maximum particle size ratio of copper and positive electrode sheets can be large. This paper provided an environmental-friendly and effective technology for separating nonferrous metals from crushed spent LFP batteries.